Midbrain catecholaminergic neurons co-express α-synuclein and tau in progressive supranuclear palsy - Erro Aguirre, María Elena; Zelaya, María Victoria; Sánchez Ruiz de Gordoa, Javier; Tuñón, María Teresa; Lanciego, José Luis (Frontiers in Neuroanatomy, 2015)
Objective: To analyze the frequency and distribution of α-synuclein deposits in progressive supranuclear palsy (PSP). Methods: The brains of 25 cases of pathologically confirmed PSP were evaluated with immunohistochemistry for α-synuclein and tau. Multiple immunofluorescent stains were applied to analyze the expression of tau and α-synuclein aggregates in catecholaminergic neurons. Patients’ clinical symptoms were retrospectively recorded. Results: Deposits α-synuclein in the form of typical Lewy bodies (LBs) were only found in two PSP cases (8%) that fulfilled the clinical subtype of PSP known as Richardson’s syndrome (RS). LBs were present in the locus ceruleus (LC), substantia nigra pars compacta (SNc), basal forebrain, amygdala and cingulated cortex in a distribution mimicking that of Parkinson’s disease (PD). Triple-immunolabeling revealed co-expression of α-synuclein and tau proteins in some tyrosine hydroxilase (TH)-positive neurons of the LC and SNc. Conclusions: There is no apparent clinical correlation between the presence of LBs in PSP. Tau protein co-aggregate with α-synuclein in catecholaminergic neurons of PSP brains suggesting a synergistic interaction between the two proteins. This is in keeping with the current view of neurodegenerative disorders as “misfolded protein diseases”.